Relationships of some attitudinal aspects of second language learning to proficiency in Pilipino - Nang, Antonio L. 1946- (1977)
The study sought to determine whether the proficiency in Pilipino as a second language of Ibang fourth year high school students of Cagayan High School is related to attitudinal aspects of second language learning such as instrumetal motivation, integrative motivation, self-concept, ideal self-concept, attitude towards the Ibang speakers and attitude towards the Pilipino speakers. The attitudinal aspects of learning Pilipino as a second language were elicited through a direct and an indirect questionnaire. Findings of the study suggested that Ibang students are instrumentally motivated to learn Pilipino as a second language. Instrumental motivation ranked higher than integrative motivation.
Appendices: Leaves 51-92
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Filipino language -- Study and teaching -- Ibanag students